Artificial selection in human‐wildlife feeding interactions. Issue 9 (4th August 2022) - Griffin, Laura L.; Haigh, Amy; Amin, Bawan; Faull, Jordan; Norman, Alison; Ciuti, Simone
Abstract: The artificial selection of traits in wildlife populations through hunting and fishing has been well documented. However, despite their rising popularity, the role that artificial selection may play in non‐extractive wildlife activities, for example, recreational feeding activities, remains unknown. If only a subset of a population takes advantage of human‐wildlife feeding interactions, and if this results in different fitness advantages for these individuals, then artificial selection may be at work. We have tested this hypothesis using a wild fallow deer population living at the edge of a capital city as our model population. In contrast to previous assumptions on the randomness of human‐wildlife feeding interactions, we found that a limited non‐random portion of an entire population is continuously engaging with people. We found that the willingness to beg for food from humans exists on a continuum of inter‐individual repeatable behaviour; which ranges from risk‐taking individuals repeatedly seeking and obtaining food, to shyer individuals avoiding human contact and not receiving food at all, despite all individuals having received equal exposure to human presence from birth and coexisting in the same herds together. Bolder individuals obtain significantly more food directly from humans, resulting in early interception of food offerings and preventing other individuals from obtaining supplemental feeding. Those females that beg consistently also produce significantly heavier fawns (300–500 g heavier), which may provide their offspring with a survival advantage. This indicates that these interactions result in disparity in diet and nutrition across the population, impacting associated physiology and reproduction, and may result in artificial selection of the begging behavioural trait. This is the first time that this consistent variation in behaviour and its potential link to artificial selection has been identified in a wildlife population and reveals new potential effects of human‐wildlife feeding interactions in other species across both terrestrial and aquatic habitats. Abstract : Human‐wildlife feeding interactions are increasingly popular, yet the role that they may play in the artificial selection of behavioural traits in wildlife populations remains unexplored. This work begins to unravel the complex dynamics and impacts of these interactions, opening up new dimensions for human‐wildlife studies.